Analysis of different proximity potentials applied to the 12C+12C reaction - Abdul Aziz, Azni (AIP Publishing, 2021)
The 12C+12C fusion reaction plays a major role in the nucleosynthesis process of the star. However, this reaction takes place at extremely low energies where a direct experimental measurement of the reaction cross sections is almost impossible. Various theoretical developments have been put forward to predict the fusion cross section at such low energies. One of the models is the proximity potential which is well known for its simplicity and numerous applications in different fields. In recent years, several refinements and modifications have been made over the original proximity potential besides several different versions of the same model are also have been proposed. The fusion cross sections of the 12C+12C reaction are calculated and analysed in the present work using different versions of the proximity potential.